Design and rationale of haemodynamic guidance with CardioMEMS in patients with a left ventricular assist device: the HEMO‐VAD pilot study. (7th January 2019) - Veenis, Jesse F.; Manintveld, Olivier C.; Constantinescu, Alina A.; Caliskan, Kadir; Birim, Ozcan; Bekkers, Jos A.; van Mieghem, Nicolas M.; den Uil, Corstiaan A.; Boersma, Eric; Lenzen, Mattie J.; Zijlstra, Felix; Abraham, William T.; et al.
Abstract: Aims: We aim to study the feasibility and clinical value of pulmonary artery pressure monitoring with the CardioMEMS™ device in order to optimize and guide treatment in patients with a HeartMate 3 left ventricular assist device (LVAD). Methods and results: In this single‐centre, prospective pilot study, we will include 10 consecutive patients with New York Heart Association Class IIIb or IV with Interagency Registry for Mechanically Assisted Circulatory Support Classes 2–5 scheduled for implantation of a HeartMate 3 LVAD. Prior to LVAD implantation, patients will receive a CardioMEMS sensor, for daily pulmonary pressure readings. The haemodynamic information provided by the CardioMEMS will be used to improve haemodynamic status prior to LVAD surgery and optimize the timing of LVAD implantation. Post‐LVAD implantation, the haemodynamic changes will be assessed for additive value in detecting potential complications in an earlier stage (bleeding and tamponade). During the outpatient clinic phase, we will assess whether the haemodynamic feedback can optimize pump settings, detect potential complications, and further tailor the clinical management of these patients. Conclusions: The HEMO‐VAD study is the first prospective pilot study to explore the safety and feasibility of using CardioMEMS for optimization of LVAD therapy with additional (remote) haemodynamic information.